Eastern Enlargement and EU-Labour-Markets: Perceptions, Challenges and Opportunities - Tito Boeri; Herbert Brücker (Institute for the Study of Labor (IZA), 2001)
This paper summarises the key findings of a recent study on the impact of Eastern Enlargement of the European Union (EU) on labour markets in the current Member States. The study focuses on three main channels, along which enlargement may affect labour markets in the EU, namely i) trade, ii) foreign direct investment, and iii) migration. A main conclusion of the study is that trade and capital movements are very unlikely to lead to an equalisation of factor prices. Thus, strong economic incentives to migration are bound to be present well beyond the date of accession. We estimate the migration potential associated with Eastern enlargement drawing on a time series model of immigration to Germany, which allows to estimate the long-term equilibrium migration potential, as well as the speed of adjustment at which the potential takes place. Our findings suggest that the long-run stock of immigrants from the CEECs-10 in the EU will increase from 0.85 in 1998 to a peak of 3.9 million persons which is expected to be reached around 30 years after the liberalisation of labour movements. Net immigration inflows in the EU are bound to increase immediately reaching a maximum of about 335,000 individuals per year, and subsequently decline to a modest 100,000 to 150,000 people per annum. Around 35% of the migrants are expected to be workers. Microeconometric exercises carried out in the context of the study indicate that such an influx of migrants will have only a moderate impact on wages and employment even in the two most affected countries, Austria and Germany. Although we are dealing with relatively small numbers, they may have an impact on wages and employment in some neighbouring regions of Austria and Germany, where immigration from the CEECs-10 is concentrated. In the final section of the paper, we argue for keeping actual migration flows from CEECs-10 under control for a transitional period. Although the chapter in the accession negotiations on the free movement of labour has been already opened, a joint position of the present EU members regarding this fundamental issue is still missing. European leaders will soon have to come to terms with this issue.
Keywords: F1; F2; J0; 330; Immigration; trade; transition; EU enlargement; EU-Erweiterung; Osteuropa; Arbeitsmarkt; Internationale Arbeitsmobilität; EU-Staaten